An intervention to enhance the supervision of health science students who struggle during work placements - Brewer, Margo; Duncanson, Kate; Gribble, Nigel; Reubenson, Alan; Hart, Alice (2021)
Supervisors are often reluctant to make an adverse assessment of the student's performance during work placements, which leads to a phenomenon known as "failure to fail". This Australian study evaluated resources designed to enhance the management of students who fail to meet the required standard of performance during work placements. Staff from a range of health disciplines evaluated the training program comprised of a half-day workshop and written guide using a questionnaire and semi-structured interviews. Staff reported renewed confidence in working with underperforming students,increased comfort with failing students who did not reach the required standards. The Staff Guide was seens as useful with all students undertaking work placements, not just underperforming students. The Student Guide was perceived as relevant to the student experience. The findings of this research are important to university educators engaged with work placements, work placement supervisors, and students who undertake work placements.